2014
DOI: 10.1016/j.mrgentox.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing of genotoxicity of 16 centralized source-waters in China by means of the SOS/umu assay and the micronucleus test: Initial identification of the potential genotoxicants by use of a GC/MS method and the QSAR Toolbox 3.0

Abstract: Only few studies were conducted to assess genotoxicity of centralized source waters in China and almost none of them dealt with the causal relationship between the genotoxic effect and genotoxicants. In this work, 16 centralized source waters in China were sampled from five river systems and genotoxicity of their organic extracts was assessed by use of the SOS/umu test for DNA-damaging effect and the miniaturized flow cytometry-based micronucleus (MN) test for chromosome-damaging effect. In addition, initial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Indeed, many researchers have reported that substances with genotoxic, and mutagenic activities are detectable in most source waters in China5101112. The Yangtze River, the largest river in Asia, with a length of 6,397 km, flows through Wuhan City, the capital of Hubei Province, with a population of 10,000,000, and is the main water supply for the city.…”
mentioning
confidence: 99%
“…Indeed, many researchers have reported that substances with genotoxic, and mutagenic activities are detectable in most source waters in China5101112. The Yangtze River, the largest river in Asia, with a length of 6,397 km, flows through Wuhan City, the capital of Hubei Province, with a population of 10,000,000, and is the main water supply for the city.…”
mentioning
confidence: 99%
“…However, as bacterial genotoxicity assays detect DNA aberration and the MN test detects chromosomal damage, the genotoxic risk screened by the bacterial tests does not necessarily overlap with the MN test results [24]. The same authors therefore suggest the application of both the MN test and a bacterial test.…”
Section: Resultsmentioning
confidence: 99%
“…All test chemicals were purchased from reliable sources and were of the highest commercially available grade. The reagents and chemical solution were prepared based on published methods 27 with slight modifications.…”
Section: Methodsmentioning
confidence: 99%